2013
DOI: 10.1016/j.bbagen.2013.03.032
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid binding to serum albumin: Molecular simulation approaches

Abstract: Molecular simulation approaches have great potentials to provide detailed biophysical insights into HSA as well as the effects of the binding of FAs or other ligands to HSA. This article is part of a Special Issue entitled Serum Albumin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(63 citation statements)
references
References 153 publications
1
62
0
Order By: Relevance
“…However, in this study, lipids were found to inhibit the accumulation of PFOS and PFOA in roots. It is reported that free fatty acids could affect the bindings between endogenous or exogenous compounds and proteins (Fujiwara and Amisaki, 2013;Spector et al, 1973). The inhibitory ability depends on the binding strength of the particular compound to proteins.…”
Section: Relationships Between the Contents Of Protein And Lipid And mentioning
confidence: 99%
“…However, in this study, lipids were found to inhibit the accumulation of PFOS and PFOA in roots. It is reported that free fatty acids could affect the bindings between endogenous or exogenous compounds and proteins (Fujiwara and Amisaki, 2013;Spector et al, 1973). The inhibitory ability depends on the binding strength of the particular compound to proteins.…”
Section: Relationships Between the Contents Of Protein And Lipid And mentioning
confidence: 99%
“…The effect of TE dose is more marked in trained than in sedentary rats, but unfortunately, the observed changes in fluorescence are not statistically significant, probably due to large inter-individual variability. The effect of testosterone dosage may be connected with modification of fluorescence of albumin, the protein involved in transport of serum endogenous steroids, as well as transport of fatty acids in the circulation [21]. Fig.…”
Section: Effect Of Endurance Training and Testosterone Treatment On Smentioning
confidence: 99%
“…Unfortunately, microscopic details concerning the dynamics of the lipid binding are currently not easily accessible to the experiment. Molecular dynamics (MD) 1 represents an interesting tool to tackle this issue [13,14] and has already been successfully employed in a few cases [15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%